9th Annual Vancouver Folk Music Festival - Vancouver Folk Music Festival Societyet al (1986)
Jericho Beach Park 9TH ANNUAL Vancouver Folk Music Festival/ -Something for Everyfolk- - A Capella - Bluegrass - Blues - Brazil - British Isles - Cajun - Caribbean - Celtic - Comedy - Cuban - Dance - Eastern European - Feminist - Filipino - Finnish - French - Gospel - Japanese - Jazz - Labour - Newfoundland - Nicaraguan - Old Timey - Punjabi - Quebecois - Spoken Word - Storytelling - Theatre - Vaudeville/ -Over 200 Performers from around the world- - The Albion Tour Band with Kathy Lesurf - Peter Alsop - Joey Ayala - Barkin' Kettle - Batucaje - Heather Bishop & Tracy Riley - Roy Bookbinder - Bob Bossin & Dennis Nichol - Greg Brown - Bob Brozman - Henry Butley - The California Cajun Orchestra - Chautauqua '86 with The Flying Karamazov Brothers - Clann na Gael - Michael Cooney - Alexander Eppler Group - David Essig - Archie Fisher - Stefan Grossman - Grupo Moncada - High Country - Igni Tawanka - Joolz - Karelia - Katari Taiko - The Kentucky Warblers - Ladies Against Women - Lapo Kabwit - Christine Lavin - The Little Mountain Band - Lo Jai - Ross McRae & Lorraine Helgerson - Celso & Carlinhos Machado - Metamora - Bill Morrissey - Charlie Murphy & Jami Sieber - Musical Ride - On to Ottawa Trek 1935-1985 - Peter Ostroushko & Tim Hennessy - U. Utah Phillips - Michael Pratt & Lynn McGown - Queen Ida & The Bon Temps Zydeco Band - Chris Rawlings - Reel World String Band - John Renbourn - The Righteous Mothers - Garnet Rogers - Shays' Rebellion - Sheila's Brush - Sileas - Fred Small - Jorge Strunz, Ardeshir Farah & Ciro Hurtado - Sweet Honey in the Rock - Swingshift - Marcia Taylor - Phil & Hilda Thomas - The Total Experience Gospel Choir - Lucie Blue Tremblay - Peter Paul Van Camp - Dave Van Ronk - Vancouver Sath presents 'Picket Line' - We Three - Nancy White & Doug Wilde - Chris Whiteley & Caitlin Hanford - Whole Loaf Theatre - Cris Williamson - Wives' Tales Story Tellers/ SUNSHINE PRINTING/ JULY 18, 19, 20 1986 Main Stage Concerts Each Evening 6 Daytime Stages Sat. & Sun. - Crafts - Foods - Little Folks Music Festival Vancouver Centennial Stage/ JERICHO BEACH PARK/ With the assistance of the TOURING OFFICE of the Canada Council/ VANCOUVER 100 city of the century/ Sponsored by the Vancouver Folk Music Festival Society with assistance from the City of Vancouver; Vancouver Board of Parks & Recreation; The Heritage Festival Society; the Province of British Columbia Cultural Services Branch; and the Department of Employment & Immigration. Thanks, Folks!/ Admission Prices: Early Bird Special (until June 21) .00 Advance Weekend Tickets (after June 21) .00 Weekend Tickets at the Gate .00 Friday Night .00 Saturday, Sunday ea. .00 Children (ages 3-12) Fri. Eve. Free; Sat./Sun. ea. .00 Youth (ages 13-18) Sat./Sun. ea. .00 Senior Citizens: free Fixed Income Tickets .00* *Contact Festival Office for details/ Tickets available in Vancouver at Black Swan Records, 2936 W. 4th Ave. (734-2828); Highlife Records, 1317 Commercial Dr. (251-6964); Zulu Records, 1869 W. 4th Ave. (738-3232); and all V.T.C./C.B.O. Outlets (280-4444). In Victoria at Victoria Folklore Centre, 539 Pandora Ave. (383-3412) and all V.T.C./C.B.O. Outlets through the province. In Seattle at Cellophane Square Records (634-2280); City People's Mercantile (324-9510) and Left Bank Books (622-0195). Further information including mail orders from the Vancouver Folk Music Festival, 3271 Main Street, Vancouver, B.C. V5V 3M6 (879-2931)/ Glen E Erikson Graphics